2022
DOI: 10.3390/diagnostics12051270
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Carcinoma with Gastrointestinal Involvement: A Systematic Review

Abstract: In this paper, we aimed to evaluate clinical and imagistic features, and also to provide a diagnostic algorithm for patients presenting with gastrointestinal involvement from hepatocellular carcinoma (HCC). We conducted a systematic search on the PubMed, Scopus and Web of Science databases to identify and collect papers oncases of HCC with gastrointestinal involvement. This search was last updated on 29 April 2022. One hundred and twenty-three articles were included, corresponding to 197 patients. The majority… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 136 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…3 A systematic review published by Urhut et al in 2022 included 192 patients, 87.3% of whom were male. 1 According to the report, the most common GI tract metastases were in the stomach (27.9%) and duodenum (27.9%). Most routes of metastasis were direct invasion and hematogenous metastasis.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…3 A systematic review published by Urhut et al in 2022 included 192 patients, 87.3% of whom were male. 1 According to the report, the most common GI tract metastases were in the stomach (27.9%) and duodenum (27.9%). Most routes of metastasis were direct invasion and hematogenous metastasis.…”
mentioning
confidence: 98%
“…After diagnosis of GI metastases, the average remaining lifespan is approximately 7.3 months. 1 Sohn et al reported the earliest case of HCC metastasis to the GI tract in 1965. The tumor was approximately of 6 cm, and located in the left hepatic lobe with portal vein invasion, and metastasized to the esophagus.…”
mentioning
confidence: 99%
See 1 more Smart Citation